PENGARUH INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KERAJINAN ROTAN DI KOTA PEKANBARU - Jayanti, Setya; Indrawati, Henny; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:This study aims to determine the effect of product innovation on purchasing decisions for rattan handicraft products in Pekanbaru City. This research method uses descriptive quantitative research. The population in this study were consumers of rattan handicrafts in Pekanbaru City. The sampling technique was accidental sampling with a sample of 52 people taken from 26 rattan crafts in Pekanbaru City. Data collection techniques using a questionnaire. The data analysis technique used simple linear regression analysis. Based on the results of the study, it was concluded that product innovation had an effect on purchasing decisions for rattan handicrafts in Pekanbaru City by 41.8%. Rattan craftsmen in Pekanbaru City should improve product innovation by adding new accessories in terms of shapes, colors and accessories that attract attention so that consumers do not feel bored, provide product guarantees so that they can increase consumer purchasing power and pay attention to product selling prices so that consumers feel that the prices are affordable and get market share in accordance with the products offered.Key Words: Purchase decision, product innovation